A Single Liver Metastasis From Adenoid Cystic Carcinoma of the Parotid Gland: Case Report - Ines Zemni MD; Nesrine Tounsi MD; Imene Bouraoui MD; Maher Slimene PhD; Ghada Sahraoui MD; Mohamed Ali Ayadi PhD; Riadh Chargui PhD; Khaled Rahal PhD (SAGE Publishing, 2019)
Adenoid cystic carcinoma is an uncommon malignant neoplasm of the salivary gland. Liver metastasis from salivary gland cancer is a rare situation. In this article, we report the case of a 29-year-old woman treated 5 years previously for adenoid cystic carcinoma of the parotid gland by surgery and radiotherapy, who presented for a large hypervascularized hepatic metastasis of 20 cm. After 3-cycle chemotherapy stability, hepatic surgery was successfully performed. The patient maintained disease-free period of 12 months after the surgical treatment. This rare case represents a therapeutic challenge for oncologists and surgeons. Through this case and a review of the literature, we try to better detail the management of this uncommon entity.